1999
DOI: 10.1089/end.1999.13.157
|View full text |Cite
|
Sign up to set email alerts
|

Piezoelectric Lithotripsy of Ureteral Stones: Influence of Shockwave Frequency on Sedation and Therapeutic Efficiency

Abstract: We recommend high frequency for piezoelectric SWL of lower ureteral calculi, especially for stones with a maximum diameter > or =8 mm. On the other hand, low-frequency SWL appears to be suitable for the treatment of upper ureteral stones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 16 publications
1
13
0
Order By: Relevance
“…Shameem et al 25 showed that the average number of shock wave and energy in kv to treat ureteric calculi were 3230 and 17.2 respectively. Two clinical studies one by Robert et al 44 and another Madbouly et al 45 have addressed the effect of varying shock wave rate on the efficiency of stone fragmentation. Skolarikos et al 46 confirmed the positive effect of lowering shock wave rates in treating ureteral stones, which indicates the necessity of large randomized clinical trials.…”
Section: Resultsmentioning
confidence: 99%
“…Shameem et al 25 showed that the average number of shock wave and energy in kv to treat ureteric calculi were 3230 and 17.2 respectively. Two clinical studies one by Robert et al 44 and another Madbouly et al 45 have addressed the effect of varying shock wave rate on the efficiency of stone fragmentation. Skolarikos et al 46 confirmed the positive effect of lowering shock wave rates in treating ureteral stones, which indicates the necessity of large randomized clinical trials.…”
Section: Resultsmentioning
confidence: 99%
“…There are few studies which investigated the effect of voltage strategy on SFR according to UC location. Robert et al [29] reported that the effects of shockwave frequency on SFRs were different according to UC location. In the study [29], SFRs were not affected by frequency in proximal UC, whereas SFR in distal UC was significantly lower at slow frequency compared to high frequency.…”
Section: Discussionmentioning
confidence: 99%
“…Robert et al [29] reported that the effects of shockwave frequency on SFRs were different according to UC location. In the study [29], SFRs were not affected by frequency in proximal UC, whereas SFR in distal UC was significantly lower at slow frequency compared to high frequency. Meanwhile, Hanna et al [30] reported difference in ureteral anatomical structure depending on ureteral location.…”
Section: Discussionmentioning
confidence: 99%
“…Various lithotriptors are currently available for shockwave lithotripsy, with the chief differences being the energy source and size of the focal point [2]. Intramuscular sedation [4], topical agents [5], analgesia pump [6], spinal anesthesia [7], general anesthesia [8], and monitored anesthesia care with intravenous sedation [3] are the variety of anesthesia techniques used for ESWL. The choice of anesthesia varies with the institution, physician and/or patient preference, and cost.…”
Section: Discussionmentioning
confidence: 99%